Concept of smart pedagogy for learning in a digital world - Daniela, Linda (Epistemological Approaches to Digital Learning in Educational Contexts, 2020)
Education as a provider of changes is always challenged to prepare the next generation for the competencies that will be needed when entering the labour market. To a certain extent, the educational system is constantly operating in reform mode because its actors have the threefold desire to preserve the knowledge they have accumulated over the course of their evolution for future generations, to anticipate future development scenarios, and to provide opportunities for future competencies. This chapter proposes ideas of perspectives on how to evaluate the enhancement of the use of technology, what aspects should be taken into account when organizing a technology-enhanced learning process, and what educators should be aware of while creating digital learning materials. One of the suggestions for the educational environment is to develop smart pedagogical principles that include not only technological pedagogical content competencies but also predictive analytical competence to operate in a smart educational environment and to promote the development of a smart society.